Top predator status and trends: ecological implications, monitoring and mitigation strategies to promote ecosystem-based management - Fortuna, Caterina Maria; Fortibuoni, Tomaso; Bueno-Pardo, Juan; Coll, Marta; Franco, Anita; Giménez, Joan; Stranga, Yolanda; Peck, Myron A.; Claver, Cristina; Brasseur, Sophie; Fernández-Corredor, Elena; Fraschetti, Simonetta; et al. (Frontiers in Marine Science, 2024)
The conservation and management of marine ecosystems hinge on a comprehensive understanding of the status and trends of top predators. This review delves into the ecological significance of marine top predators, examining their roles in maintaining ecosystem stability and functioning through an integrated analysis of current scientific literature. We first assess the efficacy of various monitoring methods, ranging from traditional field observations to cutting-edge technologies like satellite tracking and environmental DNA (eDNA) analysis and evaluating their strengths and limitations in terms of accuracy, spatial coverage, and cost-effectiveness, providing resource managers with essential insights for informed decision-making. Then, by synthesizing data from diverse marine ecosystems, this study offers a comprehensive overview of the trends affecting top predator populations worldwide. We explore the multifaceted impacts of human activities, climate change, and habitat degradation on the abundance and distribution of these key species. In doing so, we shed light on the broader implications of declining top predator populations, such as trophic cascades and altered community structures. Following a thorough assessment of successful strategies for reversing the decline of top predators, a compilation of recommendations is presented, encompassing effective governance interventions. A crucial aspect of effective ecosystem-based management is the implementation of robust monitoring strategies. Mitigation measures are imperative to reverse the adverse impacts on marine top predators. We present a comprehensive array of mitigation options based on successful case studies. These include the establishment of marine protected areas, the enforcement of fisheries regulations, and the promotion of sustainable fishing practices. We deepen the synergies between these strategies and their potential to mitigate human-induced stressors on top predator populations to safeguard their pivotal role in maintaining marine ecosystem structure and function. By examining marine top predators’ ecological significance, analyzing population trends, discussing monitoring techniques, and outlining effective mitigation strategies, we provide a comprehensive resource for researchers, policymakers, and stakeholders engaged in fostering ecosystem-based management approaches. We conclude that integrating these insights into current management frameworks will be essential to safeguard both top predators and the broader marine environment for future generations.